The role of the Fund against Catastrophic Expenditures in Health on the coverage of patients with cataract. - Mariana Navarrete-López; Esteban Puentes-Rosas; Dayana Pineda-Pérez; Haydeé Martínez-Ojeda (Instituto Nacional de Salud Pública, 2013)
Objective. To describe the effect of the Fund against Catastrophic Expenditures in Health on the provision of services for patients with cataract. Materials and methods. We used administrative dataset on hospital discharges and official figures on population to estimate the rate of care and the coverage for cataract. To estimate the variation on resources, we used data from the National System of Health Information. Results. Coverage for this disease had a significant increase between 2000 and 2010, passing from 24 per thousand cataract patients receiving attention to 58.8 per thousand. This growth is mainly due to the incorporation of cataract to the catalog of diseases covered by the Fund against Catastrophic Expenditures in Health, although this variation is not based on additional resources but in a higher productivity. The growth of services is noticeable in Aguascalientes, Coahuila, Distrito Federal and Nayarit. Conclusions. Our results suggest that policy-making based on evidence have actually brought benefits for Mexican population.